Osteopontin contributes to effective neutrophil recruitment, IL‐1β production and apoptosis in Aspergillus fumigatus keratitis. Issue 4 (26th February 2018) - Zhao, Guiqiu; Hu, Ming; Li, Cui; Lee, Jieun; Yuan, Kelan; Zhu, Guoqiang; Che, Chengye
Abstract: Fungal keratitis is a major cause of corneal ulcers, resulting in significant visual impairment and blindness. A phosphorylated glycoprotein secreted by immunocompetent cells, osteopontin (OPN) mediates cluster formation of the host fungal receptors and enhances the phagocytosis and clearance of pathogenic fungi. However, whether OPN production and function occurs in fungal keratitis is unknown. OPN expression in Aspergillus fumigatus keratitis patient corneas was assessed by quantitative polymerase chain reaction (qRT‐PCR) and immunofluorescence. Human neutrophils, THP‐1 macrophages and corneal epithelial cells (HCECs) stimulated with A. fumigatus were utilized for in vitro experiments. Mouse models of A. fumigatus keratitis were developed by intrastromal injection for in vivo experiments. Using siRNAs, neutralizing antibodies, recombinant proteins and inhibitors, the production and role of OPN in A. fumigatus infection was assessed by clinical evaluation, qRT‐PCR, immunofluorescence, western blotting and bioluminescence image acquisition. We observed increased corneal OPN expression in A. fumigatus keratitis patients and mouse models compared to controls. OPN production in response to A. fumigatus infection was dependent on LOX‐1 and Erk1/2. Compared to controls, OPN knockdown impaired proinflammatory cytokine IL‐1β production, which was dependent on 4E‐BP1. OPN knockdown decreased myeloperoxidase levels, and resulted in decreased neutrophil recruitment, higher fungal load and increased apoptosis in mouse A. fumigatus keratitis. Our results indicate that OPN is a critical component of the antifungal immune response and is essential for effective neutrophil recruitment, inflammatory cytokine production and apoptosis in A. fumigatus keratitis. Abstract : As a critical component of the antifungal immune response, osteopontin is essential for effective neutrophil recruitment, inflammatory cytokine production and apoptosis in Aspergillus fumigatus keratitis.